Wolfram als Chronist? - Matthews, A (De Gruyter, 2015)
This article in German describes how Lohengrin engages with two kinds of antecedent material: the account of Ottonian history in the Sächsische Weltchronik, which is refashioned as the context for a fictional narrative on the one hand, and the authorial image of Wolfram von Eschenbach, who is appropriated as the text’s narrator on the other.